RESPON PERTUMBUHAN DAN HASIL UBI BANGGAI (Dioscorea alata) JENIS “BAKU PUSUS” TERHADAP PEMBERIAN PUPUK ANORGANIK, ORGANIK DENGAN MULSA JERAMI PADI - Sulaiman Mansur; Henry N. Barus; Ichwan Madauna (Universitas Tadulako, 2015)
The research purpose is to study the response of growth and yield of Banggaiyam ofBaku Pususvariety under various combination of inorganic fertilizer, organic fertilizers and rice straw mulch. This study used a randomized block design (RBD) consisting of seven treatments which grouped into four based on different land slopes. Thus there were 21experimental units. There was no significant effect on growth components including growth percentage, plant height and number of shoot but it was significant on plant height at 74 days after planting (DAP).The highest plant height was 171.50 cm found in the combination of inorganic fertilizer, organic and rice straw mulch. There was alsono significant effect on the yield components except the productivity of tuber. The highest productivity was 6.33 tons ha-1shown by the combination of inorganic fertilizer, organic with rice straw mulch.Keywords : Organic, Ubi banggai (Dioscorea alata) anorganic fertilizer, Rice Straw Mulch